Variables associated with knee valgus in male professional soccer players during a single-leg vertical landing task - Vianna, M.; Metsavaht, L.; Guadagnin, E.; Franciozi, C. E.; Luzo, M.; Tannure, M.; Leporace, G. (Journal of Applied Biomechanics, 2023)
Prior studies have explored the relationship between knee valgus and musculoskeletal variables to formulate injury prevention programs, primarily for females. Nonetheless, there is insufficient evidence pertaining to professional male soccer players. Here, the aim was to test the correlation of lateral trunk inclination, hip adduction, hip internal rotation, ankle dorsiflexion range of motion, and hip isometric strength with knee valgus during the single-leg vertical jump test. Twenty-four professional male soccer players performed a single-leg vertical hop test, hip strength assessments, and an ankle dorsiflexion range of motion test. A motion analysis system was employed for kinematic analysis. Maximal isometric hip strength and ankle dorsiflexion range of motion were tested using a handheld dynamometer and a digital inclinometer, respectively. The correlation of peak knee valgus with peak lateral trunk inclination was .43 during the landing phase (P = .04) and with peak hip internal rotation was -.68 (P < .001). For knee valgus angular displacement, only peak lateral trunk inclination presented a moderate positive correlation (r = .40, P = .05). This study showed that trunk and hip kinematics are associated with knee valgus, which could consequently lead to increased knee overload in male professional soccer players following a unilateral vertical landing test.